A comparative study of tail air-deflector designs on aerodynamic drag reduction of medium-duty trucks. Issue 2 (9th March 2022) - Gao, Wei; Deng, Zhaowen; He, Yuping
With the rapid development of highway networks and logistics industry in China, medium-duty trucks have been increasingly used for highway and urban area freight transportation. The aerodynamic drag reduction of medium-duty trucks is of significant importance for improving highway transportation efficiency, enhancing fuel economy, and reducing greenhouse emissions. This paper proposes, compares and evaluates seven designs of tail air-deflector, which are devised to reduce aerodynamic drag of a medium-duty truck. The impacts of the shapes and/or configurations of tail air-deflector on the aerodynamic characteristics of the truck are studied using computational fluid dynamics (CFD) simulation. The results attained from the comparative study will provide guidelines for the design of airflow control devices for commercial vehicles to effectively reduce aerodynamic drag.